THE PROTECTION OF AVIATION BOARD NETWORKS FROM ATTACKS BY CONFLICT THEORY METHODS WITH HONEY POTS - Водопьянов, Сергей Вячеславович; Дрововозов, Владимир Иванович; Толстикова, Елена Владимировна (Ukrainian Information Security Research Journal, 2015)
The problem of protection of airborne networks fromunauthorized encroachments stands especially sharply inconnection with the necessity of the absolute providing ofsafety of flights, exception of flying incidents and preconditionsto them. For protection of network from theexternal and internal attacks it is necessary not simply toraises power and informative resources, but apply theoptimum methods of fight against a thinking opponent.The mathematical models of conflict co-operation withthe use of "honey pots" – pseudo services tightening anopponent in escalation of attack are offered in work, forcingit to expend the power and informative resources. Theconceptual model of construction of the combined systemof protection with the inculcated additional level ofprotection – network honey pot is developed. The computerdesign is conducted, the results of which testify tohigh efficiency of the developed method of protection ofnetwork.